Government Policy on the Equitable Distribution of Subsidized LPG Prices in Realizing a Just Energy Transition - Jumanah, Jumanah; Indira Sri Rejeki; Oviyanti , Oviyanti; Elvi Yunitasari; Faturohman, Faturohman (Sean Institute, 2024)
This research is motivated by the urgency of the government to realize national energy resilience with justice through the subsidy policy on 3-kilogram Liquefied Petroleum Gas (LPG). The frequent inequality in distribution and scarcity of subsidized LPG highlights the importance of policy improvement to ensure equitable energy access for vulnerable communities. The study aims to analyze the government’s role and strategies in equalizing subsidized LPG prices as part of an inclusive and sustainable energy transition agenda. The method used is a literature study with a descriptive-qualitative approach, involving analysis of policy documents, scientific journals, and official government reports. Data analysis techniques are conducted through content analysis of regulations and literature related to subsidized LPG distribution and energy justice. The findings show that the policy of equalizing the 3 kg LPG price plays a strategic role in protecting the purchasing power of the poor, encouraging cleaner energy use, and reducing the state's fiscal burden. However, the effectiveness of this policy is still hindered by uneven distribution and subsidy misuse practices. The government’s strategies in LPG subsidy reform, utilization of the Integrated Social Welfare Data (DTKS), development of the natural gas network, and involvement of local governments are considered crucial to strengthen a targeted distribution system and support the national energy transition. In conclusion, the policy of subsidized LPG price equalization significantly contributes to energy justice, but requires strengthened governance, data integration, and policy innovation to create a fair, sustainable, and inclusive energy system.